The influence of fine fractions content in non-cohesive soils on their compactibility and the CBR value - Bąk, Aleksandra; Chmielewski, Ryszard (Journal of Civil Engineering and Management, 2019)
The bearing capacity of subsoils is particularly important due to the intensive development of road and airfield pavements. Subgrade is classified due to frost susceptibility as non-frost-susceptible, low-frost-susceptible or frost-susceptible. Presented research included laboratory tests of low-frost-susceptible soils with limited potential for direct use. The main objective of this paper was focused on the study of changes of compactibility parameters and the CBR (Californian Bearing Ratio) values of silty sand (Pπ). For this purpose, seventeen soil samples with various fine fractions content (of 1.6% to 24.2%), were composed. Laboratory tests, based on soaked soil samples, encompassed the Proctor Compaction test and the CBR test. Additionally, measurements of moisture content in soaked soil samples before and after the penetration test and the displacement of annular surcharge rings while penetration test, were performed. Obtained results allowed for conclusions that penetration curves diverge from the standard curve locally, therefore direct reading of the CBR values from the penetration curves may lead to its significant overstatement. There was also noticed the dependence between the water flow in the soil and the fine fraction content. The research recognized the need for pressure measurement in soil samples during the penetration test.